ANALISIS FAKTOR PENYEBAB RENDAHNYA PENGUJIANKIR ANGKUTAN UMUM DI DINAS PERHUBUNGAN KABUPATEN MIMIKA - Fredy Elisa Saija; Yahya Nusa (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
Every human being has transportation needs for various different purposes, in land transportation we can see that the types of vehicles used to support each person's activities according to their purpose are public transportation, buses and trucks and there are still other types of vehicles so that the government through the relevant agencies carry out a driver's license test to determine whether the vehicle can be operated or not, as well as to protect against accidents that will occur and provide a sense of security when using the vehicle. Apart from that, the factors causing the low number of public transport driver tests at the Mimika Regency Transportation Service were carried out using descriptive, qualitative and quantitative methods, then the technique used to collect data was by using questionnaires and documentation to explain the structure of the relationship between many variables in the form of factors or latent variables. and to test the validity, the CFA (confirmatory factor analysis) formula is used so that it is known that the factors that have a contribution and have a strong relationship to the cause of low public transport KI testing at the Mimika Regency Transportation Service